PENGARUH SUKU BUNGA SERTIFIKAT BANK INDONESIA DAN NILAI KURS TERHADAP RISIKO SITEMATIK SAHAM PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mohamad Gita Indrawan; Raymond Raymond (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2019)
There are several factors that affect systematic risk such as inflation, exchange rates, interest rates, this is because changes that occur in these factors can result in changes in the capital market, namely the increase or decrease in stock prices. Volatility of stock prices in the capital market can potentially increase or decrease systematic risk. The purpose of this study is to examine the effect of interest rates, and exchange rates, on the financial sector stock price index. The method used in this study is using multiple linear regression. Based on the background, theoretical basis, data analysis and the results of hypothesis testing, it can be concluded that the SBI interest rate has a positive but not significant effect on stock prices and the exchange rate has a negative and not significant effect on profitability